Are Urethral Pressure Profile Measurements Effective in Diagnosing Urodynamic Stress Incontinence in Women Presenting with Stress or Mixed Urinary Incontinence? Results from a Cross-Sectional Study - Konstantinos Pantazis; Themistoklis Mikos; Sofia Tsiapakidou; Iakovos Theodoulidis; Stamatios Petousis; Konstantinos Dinas; Antonio Schiattarella; Antonio Simone Laganà; Apostolos P. Athanasiadis (Medicina, 2025)
Background and Objectives: This study aims to evaluate the relevance of urethral pressure profile (UPP) measurements in the diagnosis of urodynamic stress incontinence (USI) in women with stress and mixed urinary incontinence (SUI and MUI). Materials and Methods: A cross-sectional chart review was used. All patients who had urodynamic studies (UDSs) in the urogynecology unit of an academic hospital over the last 6 months and complained of SUI or MUI were analyzed. Clinical examination included prolapse grading with the POP-Q system. The presenting symptoms, initial diagnosis before UDS, and results from flow studies—cystometrography (CMG), which included a 1-3-5 cough test at 300–350 mL bladder filling, and urethral pressure profilometry (UPP)—were recorded. p < 0.05 was considered significant in all statistical comparison tests; receiver operator characteristic (ROC) curves were also used to determine the best predictor of SUI diagnosis. Results: In total, 57 women were included in this study, with a mean age of 60.7 (±9.3). Upon UDS, 28 women (49.1%) demonstrated USI (Group 1), while 29 women (50.9%) did not demonstrate USI (Group 2). No differences between the two groups were noted during free uroflowmetry and the filling phase of CMG. However, the women in Group 2 had a significantly lower MUCP, FUL, and post-void residual after pressure flow compared to the women in Group 1 (p = 0.038, 0.003, and 0.04, respectively, upon Student’s t test for independent parameters). The ROC analysis indicated that when using MUCP and FUL for the diagnosis of USI, the AUCs are 0.663 (0.525–0.782) and 0.756 (0.623–0.861), respectively. Conclusions: By exhibiting correlations between low MUCP/FUL and USI, UPP appears to be a valid test for USI. The value of UPP in diagnosing USI in those with SUI and MUI appears to be clinically important. Further studies are needed in non-SUI patients, in addition to SUI subgroups and various incontinence treatment groups.